Determination of the antioxidant and antifungal activities of twelve plants belonging to the Colombian coffee region - Mosquera, Oscar M. (Revista Tumbaga, 2016)
The aims of this study were determinate the antioxidant and antifungal activities of twelve plants belonging to the Colombian Coffee Region (CCR). A phytochemical characterization was performed to the hexane, dichloromethane and hexane-isopropanol (3:1) extracts. Also the antioxidant activities through Diphenylpicrylhydrazyl (DPPH•) and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS•+) methods were assayed; In addiction, the total phenolic content and the activities against the fungus Fusarium oxysporum, Fusarium solani and Mycosphaerella fijiensis Morelet were also evaluated. In this study 10 hexane-isopropanol (3:1) and 6 dichloromethane extracts as well as 1 hexane extract displayed antioxidant capacity superior to 25% through the DPPH•assay, standing out the hexane extract of Piper umbellatum (Piperaceae) with an activity of 44.8%. The extracts that showed the most important antifungal activities were the hexane-isopropanol (3:1) extract of Mikania lloensis (Asteracea) that inhibited 44.8% the growth of the fungus Fusarium oxysporum and the hexane extract of Piper pessaresanum (Piperaceae) that showed 59% of growth inhibition against Fusarium solani. Further more the Piper pessaresanum dichloromethane and hexaneisopropanol (3:1) extracts and the dichloromethane extract of Alchornea coelophylla (Euphorbiaceae) gave 100% of inhibition against the fungi Mycosphaerella fijiensis Morelet. This study is a contribution to the bioprospecting to the Colombian flora.